Fatal self-deception slaveholding paternalism in the Old South - Genovese, Eugene D. 1930-2012 (Cambridge University Press, 2011)
Slaveholders were preoccupied with presenting slavery as a benign, paternalistic institution in which the planter took care of his family and slaves were content with their fate. In this book, Eugene D. Genovese and Elizabeth Fox-Genovese discuss how slaveholders perpetuated and rationalized this romanticized version of life on the plantation. Slaveholders' paternalism had little to do with ostensible benevolence, kindness and good cheer. It grew out of the necessity to discipline and morally justify a system of exploitation. At the same time, this book also advocates the examination of masters' relations with white plantation laborers and servants - a largely unstudied subject. Southerners drew on the work of British and European socialists to conclude that all labor, white and black, suffered de facto slavery, and they championed the South's 'Christian slavery' as the most humane and compassionate of social systems, ancient and modern